Kids get coding. Coding, bugs, and fixes - Lyons, Heather (Heather K.); Tweedale, Elizabeth (Lyons, Heather (Heather K.). Kids get coding., 2017)
How do computers know what to do? They receive instructions called code with the specific steps needed to perform a task. Learn how to create codes, what happens when instructions are out of order, and how mistakes are fixed.